Ecología del Paisaje y Valores de Conservación para tres fincas propiedad de BARCA S.A, Costa Rica, en los años 2000-2005 y 2012 - Vargas-Coto, Mariana (Instituto Tecnológico de Costa Rica, 2017)
The ecology of the landscape and conservation values were analyzed for three farms owned by BARCA S.A, in the years 2000-2005 and 2012, and the company's social link with neighboring communities was diagnosed. The study was conducted in Parrita, Costa Rica. The Arcgis 10.3 and Fragstats 4.2 programs were used to analyze cartographic images. The farms were valued under FSC criteria. Birds was classified into three coverages: forest, non-forest and plantation. In 2000, forest cover predominated with 68% of the total farm, for 2005 forest plantations appeared, and accounted for 61%. In 2012, forest cover was recovered and represented 52% with an annual exchange rate of 0.18%. Around Birds changed the dynamics of the landscape. With Fragstats 4.2 the number of patches (PN), density of patches (PD) and average distance to the nearest neighbor (MNN) were calculated. Within Birds the NP increased for the three coverages in the study period. The MNN increased for forest cover in 2005. Around Birds the biggest change was from 2005 to 2012 in plantations, where the NP increased and the MNN decreased by -0.16%. In the assessment of the forests Birds was not considered With High Conservation Values (HCV). Finally, in the social analysis it was found that 30% of the inhabitants do not know the company or its projects, so a matrix was proposed to plan social projects.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2017.
Keywords: Fragmentación; Hábitat; Conservación; Fincas; Forestal; Bosques